Profil Pelajar Pancasila dalam Perspektif Pendidikan Agama Islam: doi 10.58569/jies.v1i2.575 - Rodhiyana, Mu’allimah (Journal of Islamic Education Studies, 2023)
The Pancasila Student Profile is a graduate profile that aims to demonstrate the character and competencies that are expected to be achieved and strengthen the noble values ​​of Pancasila for students and stakeholders. The Pancasila Student Profile has six competencies which are formulated as key dimensions. The six are interrelated and mutually reinforcing so that efforts to realize a complete Pancasila Student Profile require the development of the six dimensions simultaneously, not partially. The six dimensions are: 1) faith, fear of God Almighty, and have noble character, 2) global diversity, 3) work together, 4) independent, 5) critical reasoning, 6) creative. These dimensions show that the Pancasila Student Profile does not only focus on cognitive abilities, but also attitudes and behavior according to identity as a nation of Indonesia as well as citizens of the world. Indonesia's Education Vision To Realize an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila Students. Profile of Pancasila Students Indonesian students are also lifelong students who are competent, have character, and behave according to Pancasila values. Islamic Religious Education does not only teach material or concepts to be understood by students, but also enhances appreciation and practice in everyday life. Islamic Religious Education is a benchmark, how Islam and its people have played its role in various social, political and cultural aspects. Therefore, by following the development of this modern era, Islamic religious education throughout Indonesia must be increasingly developed and distributed in all areas of life in today's world. The position of Pancasila Education and Islamic Religious Education is very important, which is related to Islamic sciences which